PENINGKATAN HASIL BELAJAR OPERASI PERKALIAN DAN PEMBAGAIN BILANGAN CACAH MELALUI MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA PAPAN MUSI PADA PESERTA DIDIK KELAS IV SDI NUNBAUN SABU KOTA - Ke, Yunita Sari Ratu; Samo, Damianus D.; Bulu, Vera R. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The research problem is teacher-centered learning that only uses the lecture method, resulting in low student learning outcomes. The purpose of the research is to improve learning outcomes in multiplication and division operations of whole numbers through the contextual teaching and learning model assisted by a musi board media. This research method uses the PTK method, which consists of 4 stages: planning, implementation, observation, and reflection. The subjects in this study are the studentds of class IV A, totaling 34 students. The data collection techniques used were observation and tests, while the data analysis technique employed was quantitative descriptive. The research results show that in the first cyrcle, the percentage of teacher activity was 64%, the percentage of student activity was 74%, and the average test score of the students was 72,54 wuth a completeness percentage of 47%. Meanwhile, in the second cyrcle there was an improvement with a teacher activity percentage of 86%, a student activity percentage of 89%, and an overage test score of 86,45 with a completeness percentage of 85,29%. Based on the research resukts obtained, itcan be concluded that learning by applying the contextual teaching and learning model assisted by musi board media on multiplication and division of whole numbers can improve the learning outcomes of grade IV A students at SDI Nunbaun Sabu.